Energy, exergy, and economic evaluations of various cylindrical lithium-ion battery thermal management systems - Kumar K.; Sarkar J.; Mondal S.S. (My University, 2025)
Liquid-cooled thermal management has recently gained interest for higher battery discharge rates, although the thermo-economic consideration remains largely unexplored. Hence, this study explores 3E (energy, exergy, and economic) analysis for the thermal management of cylindrical lithium-ion battery modules for 5C discharge rate. Three microchannel-cooled battery packs (Aluminum, Phase Change Material (PCM), and foam+PCM) are compared using ternary hybrid (0.4 %Al2O3, 0.3 %MXene, 0.3 %MWCNT/water) nanofluid. At a low mass flow rate (0.1875 g/s), the foam+PCM pack achieves the lowest maximum temperature Tmax (312.15 K) and aluminum pack performs better at a higher flow rate (1 g/s). PCM pack exhibits higher Tmax and temperature gradient. Aluminum block demonstrates superior thermal efficiency (76.03 % at 0.1875 g/s) and exergy efficiency (37.9 % at 0.1875 g/s). Foam+PCM pack, although less efficient than aluminum, provides improved heat distribution and reduced exergy destruction. PCM pack, although affordable at $42.331, fails to maintain safe Tmax, while aluminum block incurs higher pump running costs. Foam+PCM pack, though initially more expensive, may result in long-term savings through increased effectiveness and lower energy usage. Copper foam-based pack outperforms aluminum and nickel foams, offering the best thermal and exergy efficiencies; hence, optimal heat management, enhanced temperature control, and energy savings make this the most effective choice. © 2025 Elsevier Ltd